India Vs Pakistan War, Triggering Nuclear War and Its Impact on The Indonesian Economy (Discourse Journal on Law and Society, 2025)
The war between India and Pakistan has had a devastating impact on the economies of both the countries directly involved and those indirectly affected. The economic impacts of this armed conflict include significant infrastructure damage, reduced production capacity, soaring inflation, rising unemployment, and reduced investment flows. This geopolitical instability has also fueled uncertainty in global financial markets, triggering a "flight to safety" phenomenon, a shift in capital and investment to countries or instruments perceived as safer, such as US government bonds or gold. For Indonesia, this situation has the potential to significantly disrupt national economic stability. One impact is a reduction in foreign direct investment (FDI) inflows, as investors tend to hold back or relocate their investments to more geopolitically stable countries. Furthermore, pressure on the rupiah exchange rate could increase due to global financial market volatility and a decline in international investor confidence. The conflict could also hamper Indonesia's export traffic, particularly to countries with close trade ties with India and Pakistan. Furthermore, these tensions could disrupt global supply chains, particularly for energy and food commodities, many of which pass through strategic trade routes. If the conflict drags on, the price of crude oil and other raw materials could potentially rise sharply, which in turn would increase domestic production costs. This would have a direct impact on inflation and public purchasing power. This situation further complicates the management of Indonesia's monetary and fiscal policies, which currently face significant challenges, such as the imminent maturities of large government debt and a still-widening state budget deficit. The government must take strategic steps to maintain domestic economic stability, strengthen foreign exchange reserves, and encourage export market diversification to reduce over-reliance on conflict-prone countries.